The Influence of Liquidity, Solvency, and Eco-Efficiency with Profitability and Dividend Policy as a Moderator on Firm Value - Mursyidin Mursyidin; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono; Djupiansyah Ganie (International Journal of Economics, Business and Innovation Research, 2023)
This article aims to explain the effect of liquidity, solvency, and eco-efficiency on profitability and how dividend policy weakens or strengthens the value of the company. This research is a literature study model with a qualitative approach, while the type of research used is library research. The company value is a measure of investors' interest in investing their capital, and the value of the company is reflected in how much the company implements disclosure of financial statements and social and environmental programs and attaches importance to the welfare of shareholders. Firm value can be viewed through the company's ability to manage debt and provide benefits to the environment, which can affect the level of company value. Companies must evaluate their business activities to maintain and increase profits because repeated losses will affect market confidence or investor decisions about the company.